PRODUCTION OF SEEDLINGS OF COLUBRINA GLANDULOSA PERKINS WITH DRILLING WASTE FROM OIL WELLS AND MYCORRHIZAL INOCULATION - Camara, Rodrigo; Ribeiro, Júlio César; Pereira, Marcos Gervasio; Silva, Ana Caroline Rodrigues; Oliveira Filho, Joel Quintino; Zonta, Everaldo (Floresta, 2021)
Oil exploration, whether onshore or offshore, results in residues from the drilling of wells, called gravel. The use of this environmental liability in the production of seedlings for forest restoration could contribute to an appropriate destination for this waste. In the present study, the objective was to evaluate the effect of the substrate formulated with gravel, with and without inoculation with arbuscular mycorrhizal fungi (AMF), on the growth and nutritional status of seedlings of Colubrina glandulosa. The design used was completely randomized in a 5x2 factorial scheme, with five gravel doses (0, 5, 10, 15, and 20%), with and without inoculation with a mixture of AMF spores (Gigaspora margarita¸ Rhizophagus clarus, and Dentiscutata heterogama) with six repetitions, totaling 60 experimental units. Height (H) and stem diameter (SD) were evaluated at 30, 60, 90, and 120 days after seedling transplantation, when the plants were sectioned in shoots (branches + leaves) and roots, to determine dry biomass of shoots (DMS) and of roots (DMR), leaf area index (LAI), rate of length of fine roots colonized by AMF (COL), and chemical composition. The substrate obtained with the application of the lowest gravel dose (5%), without the mycorrhizal inoculation, provided significant increments in H, SD, LAI, DMS, DMR, and COL of the seedlings of Colubrina glandulosa, when compared to the other gravel doses and the presence of mycorrhizal inoculation, 120 days after seedling transplantation.